Household Tobacco Smoke Exposure as a Predictor of Child Stunting: A Multivariate Analysis in Indonesia - Mikawati Mikawati; Kens Napolion; M.Thabran Talib (PT.Mantaya Idea Batara, 2025)
Introduction: Stunting remains a significant public health concern in low- and middle-income countries, including Indonesia, with determinants that extend beyond nutrition and infection. Environmental exposures, particularly household tobacco smoke, have emerged as important contributors to impaired child growth. This study examined the association between household tobacco smoke exposure and stunting among children under five years of age, adjusting for selected biological and environmental factors. A cross-sectional analytical study was conducted among 420 children aged 6–59 months in urban and peri-urban areas of Makassar, Indonesia. Data collection involved caregiver interviews and standardized anthropometric measurements. Stunting was defined as a height-for- age z-score below −2 standard deviations according to World Health Organization (WHO) Child Growth Standards. Household tobacco smoke exposure was assessed through caregiver self-report. Multivariate logistic regression analysis was used to estimate adjusted odds ratios (AORs) and 95% confidence intervals (CIs). The overall prevalence of stunting was 36.7%. Children exposed to household tobacco smoke had a higher prevalence of stunting compared to those unexposed (45.7% vs. 26.6%). After adjustment for potential confounders, tobacco smoke exposure was significantly associated with increased odds of stunting (AOR = 2.30; 95% CI: 1.53–3.48; p < 0.001). Stunting was common among the study population, and the association between household tobacco smoke exposure and stunting persisted after adjustment for relevant factors. Child age was also significantly associated with stunting, while other variables were not statistically significant. In conclusion, household tobacco smoke exposure is significantly associated with stunting among children under five in Indonesia. These findings underscore the need to incorporate environmental and behavioral risk factors, including tobacco control, into comprehensive strategies for stunting prevention.